2019
DOI: 10.1093/hmg/ddz151
|View full text |Cite
|
Sign up to set email alerts
|

Combining P301L and S320F tau variants produces a novel accelerated model of tauopathy

Abstract: Understanding the biological functions of tau variants can illuminate differential etiologies of Alzheimer’s disease (AD) and primary tauopathies. Though the end-stage neuropathological attributes of AD and primary tauopathies are similar, the etiology and behavioral outcomes of these diseases follow unique and divergent trajectories. To study the divergent physiological properties of tau variants on a uniform immunogenetic background, we created somatic transgenesis CNS models of tauopathy utilizing neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…Consistent with reports from other laboratories (Ramsden et al, 2005 ; Schindowski et al, 2006 ), we observed that mice with accelerated NFT deposits also developed rapid memory impairment (Koller et al, 2019 ). While our results were consistent with human data (reviewed in Nelson et al, 2012 ), other preclinical studies have shown that tau conformers, independent of NFT, underlie memory deficits and network alterations (Santacruz et al, 2005 ; Bolós et al, 2017 ; Green et al, 2019 ).…”
Section: Neuroplasticity Loss In Ad and Related Tauopathiessupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with reports from other laboratories (Ramsden et al, 2005 ; Schindowski et al, 2006 ), we observed that mice with accelerated NFT deposits also developed rapid memory impairment (Koller et al, 2019 ). While our results were consistent with human data (reviewed in Nelson et al, 2012 ), other preclinical studies have shown that tau conformers, independent of NFT, underlie memory deficits and network alterations (Santacruz et al, 2005 ; Bolós et al, 2017 ; Green et al, 2019 ).…”
Section: Neuroplasticity Loss In Ad and Related Tauopathiessupporting
confidence: 93%
“…Gliosis closely follows the development of tauopathy in transgenic mouse models (Ramsden et al, 2005 ; Schindowski et al, 2006 ; Yoshiyama et al, 2007 ; de Calignon et al, 2012 ; Maeda et al, 2016 ). We developed several mouse models of tauopathy in our lab to understand how gliosis is differentially regulated in the presence of intracellular phosphorylated tau and NFT inclusions (Koller et al, 2019 ). These models express different human mutant tau constructs following neonatal delivery of recombinant adeno-associated viruses (AAV).…”
Section: Neuroplasticity Loss In Ad and Related Tauopathiesmentioning
confidence: 99%
“…Using a panel of FTD-associated tau mutants, HDAC6 showed increased binding to P301L and S320F mutations. The exact properties of these particular mutants that enable more robust engagement with HDAC6 is not clear, however a recent study indicated synergistic aggregation and seeding of the P301L and S320F mutations [59][60][61] . Our data suggest that HDAC6 may preferentially target specific aggregate-prone conformations, or strains, via a chaperone bridge, as mutations that abrogate tau-chaperone binding also diminished tau-HDAC6 binding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The tau inclusions that form are insoluble, Thioflavin S positive, and show fibrillar structure by electron microscopy (EM) [ 10 ]. Notably, BSCs are highly predictive of results obtained upon transgenic or rAAV-mediated expression of tau in rodent models [ 35 ].…”
Section: Introductionmentioning
confidence: 99%